Rozmowy młodzieży z rodzicami. Narracja z perspektywy młodzieży - Karmolińska-Jagodzik, Ewa (Studia Edukacyjne, 2017)
Young people have a strong need to be in good relationships with their parents. They learn from them most. Parents are the starting point and often the turning point in many crisis situations. In the process of formulating their identity, young people need more and more living space outside their family home to carry out their development tasks. But it is hard not to talk to parents. Each conversation may take different forms. This article shows the specificityof the ongoing discussions between young people and their parents in a contemporary family home. Based on my research, I point out not only conflictsituations in the contemporary family, but I also explain the importance of intergenerational conflict,its specificity. I moreoverindicate both normative and opportunistic aspects of the dialogues carried out by young people. I am going to show we need a conversation and what its strength is. Even if I seem to point to the negative aspects of conversation, it remains an indispensable, or even a therapeutic element of support for both young people and their parents.